Influence Of Orchard Management Strategies On Growth, Yield, Quality And Leaf Mineral Concentrations In Cherry Cv. ‘bigarreau Noir Gross (Misri)’ (Applied Biological Research, 2013)
The effect of various orchard floor management treatments of young cherry  trees (Prunus avium L) cv. Bigarreau Noir Gross (Misri) on growth, yield,  quality and leaf mineral element concentrations were investigated during the  year 2008 and 2009 at Ambri Research Station, Pahnoo, Shopian SKUAST-K  Shalimar. The treatments included growing of kharif- and rabi-sown intercrops  viz., maize, pea, strawberry, cabbage, red clover, french bean and oats along  with a control (clean cultivation). The results revealed that young cherry trees  intercropped with leguminous crops (pea, red clover or french bean) performed  better with respect to growth, yield, quality and leaf mineral element  concentration than control or intercropping with heavy feeder crops  (strawberry, cabbage, oats or maize). Higher produce and heavier fruit was  obtained from the cherry trees intercropped with pea followed by red clover  and french bean. The firmness, colour and ascorbic acid content were high in  fruits from cherry trees intercropped with red clover or French bean.
Keywords: Apple; intercrops; mineral elements; orchard management; legumes; heavy feeder crops